Current Issues in the Design and Conduct of Monetary Policy - Khan, Mohsin (IMF Working Papers; Working Paper, 2003)
Movements in global capital during the late 1990s and the greater emphasis on price stability led many countries to abandon fixed exchange rate regimes and to design institutions and monetary policies to achieve credibility in the goal of lowering inflation. Such recent developments have brought to the forefront the idea that freely mobile capital, independent monetary policy, and fixed exchange rates form an "impossible trinity." It is possible to have two of these policies, but not all three. Inflation-targeting regimes being adopted by many countries provide a way of resolving this dilemma.